Perinatal health among migrant women: A longitudinal register study in Finland 2000-17 - Heini Väisänen; Hanna Remes; Pekka Martikainen (Elsevier, 2022)
Migrants often have better health than the native-born population ('healthy immigrant effect'), although the effect tends to attenuate over time since migration. However, following the weathering hypothesis, migrants may have worse health due to a combination of discrimination and poorer financial conditions faced by many of them. Yet, little is known about interactions between migrant origin and individual socioeconomic status or the time spent in the host country in relation to reproductive health. We use Finnish register data of 491,532 women and 948,616 births spanning years 2000-17 to longitudinally study the association between the country of birth and perinatal outcomes (preterm birth, unplanned C-section, episiotomy and spontaneous vaginal birth); the interaction of country of birth with household income; and the effect of time since migration using random intercept logistic regression models. We show that a 'healthy immigrant effect' largely does not exist for perinatal outcomes apart from migrants from a few high-income countries. Instead, in particular women from poorer countries tended to fare worse than native women. Often, the effect of the country of birth did not differ by household income, or the patterns were not clear. The impact of time since immigration was complex and dependent on country of birth and the outcome studied, but showed an increase in risk of preterm birth among migrants from low- and lower-middle-income countries compared to those born in Finland. Discrimination, language barriers in seeking care or refugee experiences are among some of the possible mechanisms explaining the worse perinatal health of migrants from poorer countries. The inequalities observed in a global scale in countries' economic outcomes may reproduce themselves as reproductive health inequalities among migrants living in wealthy countries.